2014
DOI: 10.1177/1559827614550277
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology and Physical Health

Abstract: Positive psychology is the scientific study of a healthy and flourishing life. The goal of positive psychology is to complement and extend the traditional problem-focused psychology that has proliferated in recent decades. Positive psychology is concerned with positive psychological states (eg, happiness), positive psychological traits (eg, talents, interests, strengths of character), positive relationships, and positive institutions. We describe evidences of how topics of positive psychology apply to physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 69 publications
(112 reference statements)
3
67
0
1
Order By: Relevance
“…The present findings include several strengths similar to items from the taxonomy of character strengths in positive psychology, that is perseverance, kindness, bravery, humour and gratitude . However, most studies on character strengths have included participants from the general population . The present study therefore adds to knowledge about the strengths and their applicability reported by people with chronic illness.…”
Section: Discussionmentioning
confidence: 97%
“…The present findings include several strengths similar to items from the taxonomy of character strengths in positive psychology, that is perseverance, kindness, bravery, humour and gratitude . However, most studies on character strengths have included participants from the general population . The present study therefore adds to knowledge about the strengths and their applicability reported by people with chronic illness.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted, however, that this area of study has also faced some criticism, as positive psychology behaviors such as forgiveness may not be functional in all contexts and circumstances (McNulty and Fincham, 2012). Nevertheless, several studies have shown that human flourishing is related to mental and physical health (e.g., Park et al, 2016), and reviews and meta-analyses have shown that positive psychology interventions work in terms of improving well-being and (academic) performance (Sin and Lyubomirsky, 2009;Durlak et al, 2011;Mongrain and Anselmo-Matthews, 2012;Waters, 2012). Thus, making sure that people receive positive psychology interventions, especially those relating to purpose in life, seems a viable and inexpensive way to help millions of people to have a better and healthier life (Menec, 2003;Seligman et al, 2005).…”
Section: Ikigai Meaning In Life and Life Craftingmentioning
confidence: 99%
“…It also reflected people’s ambitious outlook after the Second World War, when health and peace were seen as inseparable (83, 84). Since then, this shift has seen a major growth in the last 30 years, primarily in areas of positive health and psychology (8892). …”
Section: Defining Healthmentioning
confidence: 99%